Proyecto de negocio internacional para la exportación de MIX Verde hacia España (2021)
Green juice has become a breakfast staple, and it's not hard to see because it's rich in nutrients and vitamins, while it can provide multiple health benefits, and it's easy to prepare. Assuming that the purpose of this study is aimed at determining the feasibility of carrying out an export process of natural juice (Green Mix) from Santa Marta (Colombia) to Spain, taking as a reference the trends in global consumption of healthy products, it is commented that this document has analyzed aspects related to the market and competition, an operation plan in accordance with the required process and a financial plan, which together develop the bases for meeting this objective; concluding that the potential viability of carrying out the export of this product to the Iberian market has been identified